THE INFLUENCE OF ELECTRONIC WORD OF MOUTH ON CONSUMER TRUSTWORTHINESS AND PURCHASE INTENTION (Survey on Followers Instagram of @Zaloraid) - Dewa Ayu Mitha Avriyanti; Andriani Kusumawati; Inggang Perwangsa Nuralam (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This research aimed to (1)explaining the influence of Electronic Word of Mouth on Consumer Satisfaction (2)explaining the influence of Electronic Word of Mouth on Purchase Intention (3)explaining the influence of Consumer Satisfaction on Purchase Intention. The type of this research is explanatory research with quantitative approach. The variables of the research are Electronic Word of Mouth, Consumer Trustworthiness, and Purchase Intention. The sampling technique for this research was using purposive sampling and the data collection method by distributing online questionnaire to 116 respondents according to population criteria. Data analysis used descriptive analysis and path analysis. The results showed that Electronic Word of Mouth significant influence on Consumer Trustworthiness, Electronic Word of Mouth has significant influence on Purchase Intention, and Consumer Trustworthiness has significant influence on Purchase Intention. Based on the results of this research, Zalora should improve the information throughout Zalora’s Social Media evenly and improve the quality of service, so the activities of Electronic Word of Mouth (eWoM) such as consumer reviews are increasing and it affect to increas the new member of Zalora’s consumer. Kеywords: Electronic Word of Mouth, Consumer Trustworthiness, Purchase Intention, Online Shopping. АBSTRАK Penelitian ini bertujuan untuk (1) menjelaskan pengaruh Electronic Word of Mouth terhadap Consumer Trustworthiness, (2) menjelaskan pengaruh Consumer Trustworthiness terhadap Purchase Intention, (3) menjelaskan pengaruh Electronic Word of Mouth terhadap Purchase Intention. Jenis penelitian ini adalah eksplanatori (explanatory research) dengan pendekatan kuantitatif. Variabel pada penelitian ini terdiri dari Electronic Word of Mouth, Consumer Trustworthiness, Purchase Intention. Teknik pengambilan sampel yang digunakan adalah purposive sampling dan metode pengumpulan data melalui kuesioner secara online kepada 116 responden yang sesuai dengan kriteria populasi. Analisis data yang digunakan adalah analisis deskriptif dan analisis jalur (path analysis). Hasil penelitian menunjukkan bahwa Electronic Word of Mouth berpengaruh secara signifikan terhadap Consumer Trustworthiness, Electronic Word of Mouth memiliki pengaruh yang signifikan terhadap Purchase Intetion, Consumer Trustworthiness berpengaruh signifikan terhadap Purchase Intetion. Berdasarkan hasil penelitian, sebaiknya Zalora meningkatkan kembali informasi pada seluruh Social Media Zalora secara merata dan meningkatkan kualitas pelayanan, agar kegiatan Elektronic Word of Mouth (eWoM) seperti review dari konsumen semakin meningkat karena hal itu berpengaruh dalam meningkatkan jumlah konsumen baru Zalora. Kаtа Kunci: Electronic Word of Mouth, Consumer Trustworthiness, Purchase Intention, Online Shopping.